Juridical Analysis of Corruption in the State Budget (Study of District Court Decision Number 49/Pid.Sus-Tpk/2018/Pn.Jkt.Pst) - Setyawan, Iwan; Katherine, Katherine; Susanti, Nia; Muhlizar, Muhlizar (ARBITER: Jurnal Ilmiah Magister Hukum, 2023)
This article aims to examine the regulation of criminal acts of corruption in the management of State funds based on Law No. 31 of 1999 in conjunction with Law No. 20 of 2001, analyzing the judge's considerations in District Court Decision Number 49/Pid.Sus-TPK/2018/PN.Jkt.Pst which is in line with the KUHAP and Law no. 31 of 1999 in conjunction with Law no. 20 of 2001, as well as evaluating the verdict given by the judge in District Court Decision Number 49/Pid.Sus-TPK/2018/PN.Jkt.Pst by Law no. 31 of 1999 in conjunction with Law no. 20 of 2001. The focus of the problem is the regulation of criminal acts of corruption in the State budget based on Law No. 31 of 1999 in conjunction with Law No. 20 of 2001, the judge's considerations in District Court Decision Number 49/Pid.Sus-TPK/2018/PN.Jkt.Pst which are in line with the KUHAP and Law no. 31 of 1999 in conjunction with Law no. 20 of 2001, as well as the verdict handed down by the judge in District Court Decision Number 49/Pid.Sus-TPK/2018/PN.Jkt.Pst by Law no. 31 of 1999 in conjunction with Law no. 20 of 2001. This research uses criminal theory and prosecution theory. Data was collected through library search techniques and analyzed qualitatively. The results of this study concluded that the Panel thought that the Defendant was legally and convincingly proven guilty of committing a criminal act of corruption by Article 3 of Law Number 31 of 1999 as amended by Law Number 20 of 2001.